Sirtuin 5 Regulates Proximal Tubule Fatty Acid Oxidation to Protect against AKI - Chiba, Takuto; Peasley, Kevin D; Cargill, Kasey R; Maringer, Katherine V; Bharathi, Sivakama S; Mukherjee, Elina; Zhang, Yuxun; Holtz, Anja; Basisty, Nathan; Yagobian, Shiva D; Schilling, Birgit; Goetzman, Eric S; et al. (Journal of the American Society of Nephrology, 2019)
The primary site of damage during AKI, proximal tubular epithelial cells, are highly metabolically active, relying on fatty acids to meet their energy demands. These cells are rich in mitochondria and peroxisomes, the two organelles that mediate fatty acid oxidation. Emerging evidence shows that both fatty acid pathways are regulated by reversible posttranslational modifications, particularly by lysine acylation. Sirtuin 5 (Sirt5), which localizes to both mitochondria and peroxisomes, reverses post-translational lysine acylation on several enzymes involved in fatty acid oxidation. However, the role of the Sirt5 in regulating kidney energy metabolism has yet to be determined. We subjected male Sirt5-deficient mice (either +/- or -/-) and wild-type controls, as well as isolated proximal tubule cells, to two different AKI models (ischemia-induced or cisplatin-induced AKI). We assessed kidney function and injury with standard techniques and measured fatty acid oxidation by the catabolism of C-labeled palmitate to CO . Sirt5 was highly expressed in proximal tubular epithelial cells. At baseline, knockout ( ) mice had modestly decreased mitochondrial function but significantly increased fatty acid oxidation, which was localized to the peroxisome. Although no overt kidney phenotype was observed in mice, mice had significantly improved kidney function and less tissue damage compared with controls after either ischemia-induced or cisplatin-induced AKI. This coincided with higher peroxisomal fatty acid oxidation compared with mitochondria fatty acid oxidation in the proximal tubular epithelial cells. Our findings indicate that Sirt5 regulates the balance of mitochondrial versus peroxisomal fatty acid oxidation in proximal tubular epithelial cells to protect against injury in AKI. This novel mechanism might be leveraged for developing AKI therapies.